Gender Differences in Influencer Advertisements on Instagram: A Multimodal Perspective - Anderson Hidarto; Aryani Andrieza (Universitas Sanata Dharma, 2022)
Congruent with the rapid development of internet users worldwide, social media advertising has been mushrooming on various social network platforms, including Instagram. Among the many forms of advertising that marketers have relied on is influencer advertising, which pertains to hiring popular Instagram influencers to endorse particular products or services on their Instagram accounts. This study explores how these Instagram influencers use both texts and images to convey their advertising messages. Further, the study explores the differences in how male and female influencers construct their endorsement posts. A total of 20 advertisement posts were collected from 10 influencers and were analyzed from the multimodal approach integrated with the concepts of linguistic metafunctions in Systemic Functional Linguistics. Then, the gender differences in texts and images were elaborated. It is shown that interpersonal language dominates the language used in the captions, despite the specific differences in the linguistic items used by men and women. Likewise, in the images, the influencers seem to consistently put the spotlight on themselves rather than on the products to captivate the followers' attention. The findings of this study will eventually contribute to the literature on advertising language and multimodal analysis.